The substantial hospitalization burden of influenza in central China: surveillance for severe, acute respiratory infection, and influenza viruses, 2010–2012. Issue 1 (10th November 2013) - Yu, Hongjie; Huang, Jigui; Huai, Yang; Guan, Xuhua; Klena, John; Liu, Shali; Peng, Youxing; Yang, Hui; Luo, Jun; Zheng, Jiandong; Chen, Maoyi; Peng, Zhibin; et al.
<x xml:space="preserve">Abstract</x> Background Published data on influenza in severe acute respiratory infection (SARI) patients are limited. We conducted SARI surveillance in central China and estimated hospitalization rates of SARI attributable to influenza by viral type/subtype. Methods Surveillance was conducted at four hospitals in Jingzhou, China from 2010 to 2012. We enrolled hospitalized patients who had temperature ≥37·3°C and at least one of: cough, sore throat, tachypnea, difficulty breathing, abnormal breath sounds on auscultation, sputum production, hemoptysis, chest pain, or chest radiograph consistent with pneumonia. A nasopharyngeal swab was collected from each case‐patient within 24 hours of admission for influenza testing by real‐time reverse transcription PCR. Results Of 17 172 SARI patients enrolled, 90% were aged <15 years. The median duration of hospitalization was 5 days. Of 16 208 (94%) SARI cases tested, 2057 (13%) had confirmed influenza, including 1427 (69%) aged <5 years. Multiple peaks of influenza occurred during summer, winter, and spring months. Influenza was associated with an estimated 115 and 142 SARI hospitalizations per 100 000 during 2010–2011 and 2011–2012 [including A(H3N2): 55 and 44 SARI hospitalizations per 100 000; pandemic A(H1N1): 33 SARI hospitalizations per 100 000 during 2010–2011; influenza B: 26 and 98 hospitalizations per 100 000], with the highest rate among children aged 6–11 months (3603 and 3805 hospitalizations per 100 000 during 2010–2011 and 2011–2012, respectively). Conclusions In central China, influenza A and B caused a substantial number of hospitalizations during multiple periods each year. Our findings strongly suggest that young children should be the highest priority group for annual influenza vaccination in China.